Diagnostic value of the 16‐detector row multislice spiral computed tomography for the detection of coronary artery stenosis in comparison to invasive coronary angiography - Deetjen, Anja G. (Clin Cardiol, 2007)
OBJECTIVES: The aim of this study was to determine the diagnostic accuracy of 16‐slice multislice spiral computed tomography (MSCT) of the coronaries and to provide data in a real clinical setting. Previous 16‐slice MSCT studies presented data excluding patients with calcification, vessels of < 1.5 or 2 mm, and segments with impaired image quality. By including these data for 16‐slice MSCT, a direct comparison with new data from 64‐slice MSCT is possible. METHODS AND RESULTS: Sixty two patients with suspected or known coronary artery disease (CAD) were prospectively enrolled and underwent computed tomography angiography (CTA) and invasive coronary angiography (ICA). All vessels were evaluated for the presence of a significant coronary artery stenosis (>50%) using the American Heart Association (AHA) 15‐segment model. From the evaluation of 917 segments, sensitivity, specificity, and positive and negative predictive value (NPV) (positive predictive value [PPV] and NPV) for the presence of relevant coronary stenosis were 73, 98, and 71 and 98% per segment and 94, 90, and 91 and 93% per patient, respectively. The influence of age, gender, body surface area (BSA), heart rate (HR), stents, and Ca(2+)‐score value was analyzed. High Ca(2+)‐score values were the only statistically significant predictor for impaired diagnostic accuracy. CONCLUSIONS: In summary, CTA with evaluation of all vessel segments in a broad spectrum of patients allowed accurate and fast noninvasive coronary artery evaluation, including evaluation of stented segments. These data are very similar to those published recently for 64‐slice scanners. Copyright © 2007 Wiley Periodicals, Inc.